1999
DOI: 10.1093/glycob/9.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of  1,2 galactosyltransferase and UDP-galactose transporter efficiently galactosylates N- and O-glycans in Saccharomyces cerevisiae

Abstract: We have studied in vivo neo-galactosylation in Saccharomyces cerevisiae and analyzed the critical factors involved in this system. Two heterologous genes, gma12 + encoding α1,2-galactosyltransferase (α1,2 GalT) from Schizosaccharomyces pombe and UGT2 encoding UDP-galactose (UDP-Gal) transporter from human, were functionally expressed to examine the intracellular conditions required for galactosylation. Detection by fluorescence labeled α-galactose specific lectin revealed that 50% of the cells incorporated gal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…In this strain, both in vitro UDP-Gal transport activity and in vivo galactosylation at the cell surface were confirmed (Roy et al, 1998). A similar strain construct, MKY12, in which the gma12 + gene was functionally expressed under the background of a common laboratory strain W303-1A, showed a detectable level of in vitro UDP-Gal transport activity (Kainuma et al, 1999). In addition, we found that overexpression of human derived UDP-Gal transporter resulted in a significant increase of UDP-Gal transport activity as well as in vivo galactosylation on both N-and O-linked oligosaccharides.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…In this strain, both in vitro UDP-Gal transport activity and in vivo galactosylation at the cell surface were confirmed (Roy et al, 1998). A similar strain construct, MKY12, in which the gma12 + gene was functionally expressed under the background of a common laboratory strain W303-1A, showed a detectable level of in vitro UDP-Gal transport activity (Kainuma et al, 1999). In addition, we found that overexpression of human derived UDP-Gal transporter resulted in a significant increase of UDP-Gal transport activity as well as in vivo galactosylation on both N-and O-linked oligosaccharides.…”
Section: Introductionmentioning
confidence: 52%
“…Strains MKY6, MKY12, MKY13 and MKY14 were constructed as described previously (Kainuma et al, 1999). Briefly, MKY6 harbours an integrated gma12+ gene encoding a1,2-galactosyltransferase from Sz.…”
Section: Plasmid and Strain Constructionsmentioning
confidence: 99%
See 3 more Smart Citations